A COMPARATIVE STUDY: ONE VILLAGE ONE PRODUCT (OVOP) AS AN ENGINE OF LOCAL ECONOMIC DEVELOPMENT IN JAPAN AND INDONESIA - Arin Widiyanti (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2018)
The One Village One Product (OVOP) is a voluntary local community movement that drives the Local Economic Development (LED) and the revitalization effort, which was initiated in 1979 in Oita prefecture, Japan. The research examines the OVOP approach by comparing the OVOP program in Indonesia, particularly the case study of OVOP in Sragen regency, Central Java province, to the original OVOP program of Oita prefecture in Japan. This study takes Oita as the observation, since Oita is considered as the region in which the OVOP concept is conducted successfully. For that reason, this research is aimed for taking a lesson to be learned and to be applied in Indonesia, in which in Indonesia the respective concept has not so far succeeded. The key feature of the OVOP implementation in Oita is the bottom-up approach that is well adapted in Japanese experience of local economic development. The case studies illustrated that, when it was transferred to Indonesia, the principles of OVOP were not directly copied from the OVOP in Japan. In Indonesia, OVOP was reconfigured into a government program with a top-down approach. This study will mainly focus on comparing both study cases qualitatively. Basically the characteristics OVOP literature reviews are: the History of the Oita-Japan OVOP program, the study about specific programs outside of Japan based on the Oita OVOP model and the study that compares Oita-type programs across countries. However, this paper found a few studies which focus on the particular role of private companies in initiating and maintaining the OVOP programs, as distributors and suppliers, this topic become main research object for the research